Testamentetotak [electronic resource] : Josuab aglanginit, esterib aglangit tikkilugit. - Erdmann, Friedrich, 1810-1873.; Moravian Church. (Stolpen [Germany] : G. Winterib Nênerlauktangit, 1869)
Translation of "Joshua to Esther in the language of Labrador" by Friedrich Erdmann--Bibliographies of the Languages of the North American Indians / J.C. Pilling, vol. I. "Printed for the British and Foreign Bible Society in London, for the use of the Moravian Mission in Labrador." Electronic reproduction. Mode of access: Internet. 44